The Diversity of Epiphytic Wild Orchids in Mallawa Resort Area of Bantimurung Bulusaraung National Park, South Sulawesi, Indonesia - Hiola, St. Fatmah; Dirawan, Gufran D; Caronge, Muhammad Wiharto (Department of Agronomy and Horticulture, IPB University, 2015)
This research aims to report the diversity of epiphytic wild orchids in Mallawa Resort area of Bantimurung Bulusaraung National Park (BBNP), South Sulawesi, Indonesia. Exploration methods were used in this study to search and record epiphyticwild orchids in this area. The technique of data collection comprised taking pictures with a digital camera for documentation and collecting specimens of wild orchids that were unidentified at the site. The identification of orchid species was conducted by matching the morphology and characterization of epiphytic wild orchids with appropriate photographs showing details to enable identification. The results of the study showed that there were 36 species of epiphytic wild orchids to be found in the study area. The identification to species level included 10 species, there were 17 specimens that were identified to genus level, and seven specimens remained unidentified. Sympodial type orchids dominated the suite of native orchids, with 23 species.Keyword: epiphytes, Mallawa Resort, Bantimurung Bulusaraung National Park, wild orchids